Simultaneous kidney-pancreas transplantation: the Parma Center experience - Capocasale, E.; Busi, N.; Mazzoni, et al., M.P. (Acta Biomedica Atenei Parmensis, 2007)
Background and aim: Diabetes mellitus is one of the major causes of end stage renal disease. After 10-15 years from the onset 30% of diabetic patients present nephropathy, and once haemodialysis is required, morbidity is particularly high and long-term survival is lower than in non-diabetic patients. Currently, it is demonstrated that simultaneous pancreas-kidney transplantation (SPK) shows beneficial effects on patient survival, on some diabetic degenerative complications and on the quality of life. Aim of the work is to report our experience in pancreas transplantation. Methods: From June 1998 to June 2005 17 type I diabetic uremic patients underwent SPK. Donor selection considered hemodynamically stable young patients without cardiac arrest or vasopressor drug excess and with a brief Intensive Care Unit hospitalization. Average donor age was 26 years (range 16-38). The cause of death was trauma for 14 donors (82,4%) and spontaneous cerebral hemorrhage for 3 donors (17,6%). Average pancreas cold ischemic time was 716 minutes (range 320-968). Results: No patient mortality was observed. No primary or delayed graft function was observed both for pancreas and kidney. Biopsy proved the occurrence of acute rejection episode in one patient (5,8%). Five surgical (29,4%) and 2 medical (11,7%) complications developed. At a median follow-up of 36,4 months (range 4,2-88) patient survival rate was 100%. Pancreas and kidney graft survival rate was 76,5% and 94,1%, respectively. All patients referred an improvement in their quality of life. Conclusions: SPK represents a wellestablished therapy for uremic type I diabetes mellitus since it improves patient survival in selected recipients. Our experience, as reported in literature, confirm that a successful pancreas transplantation not only brings the recipient back to normal glycemic levels, but it also improves the patient’s quality of life by stabilizing some of the secondary complications of diabetes.